Step-by-step explanation:
An arithmetic sequence is given by relation as follows :
![A(n)=-6+(n-1)\dfrac{1}{5}](https://tex.z-dn.net/?f=A%28n%29%3D-6%2B%28n-1%29%5Cdfrac%7B1%7D%7B5%7D)
For the first term, put n = 1. So,
![A(1)=-6+(1-1)\dfrac{1}{5}\\\\A(1)=-6](https://tex.z-dn.net/?f=A%281%29%3D-6%2B%281-1%29%5Cdfrac%7B1%7D%7B5%7D%5C%5C%5C%5CA%281%29%3D-6)
For fourth term, put n = 4. So,
![A(4)=-6+(4-1)\dfrac{1}{5}\\\\A(4)=\dfrac{-27}{5}\\\\A(4)=-5\dfrac{2}{5}](https://tex.z-dn.net/?f=A%284%29%3D-6%2B%284-1%29%5Cdfrac%7B1%7D%7B5%7D%5C%5C%5C%5CA%284%29%3D%5Cdfrac%7B-27%7D%7B5%7D%5C%5C%5C%5CA%284%29%3D-5%5Cdfrac%7B2%7D%7B5%7D)
For tenth term, put n = 10. So,
![A(10)=-6+(10-1)\dfrac{1}{5}\\\\A(10)=-6+\dfrac{9}{5}\\\\A(10)=\dfrac{-21}{5}\\\\A(10)=-4\dfrac{1}{5}](https://tex.z-dn.net/?f=A%2810%29%3D-6%2B%2810-1%29%5Cdfrac%7B1%7D%7B5%7D%5C%5C%5C%5CA%2810%29%3D-6%2B%5Cdfrac%7B9%7D%7B5%7D%5C%5C%5C%5CA%2810%29%3D%5Cdfrac%7B-21%7D%7B5%7D%5C%5C%5C%5CA%2810%29%3D-4%5Cdfrac%7B1%7D%7B5%7D)
Hence, the correct option is (C).
X = [-(-8) +/- sqrt((-8)^2 -4*41)] / 2
x = ( 8 + sqrt (-100) / 2 and (8 - sqrt(-100) / 2
4 +or- 5i
Answer:
Step-by-step explanation:
rewrite as multiplication
look to factor
, difference of 2 squares and perfect square
, finish factoring and simplify
2(x+3)
Answer: C
Step-by-step explanation: